2019
DOI: 10.28992/ijsam.v3i1.69
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility as Economic Mechanism for Creating Firm Value

Abstract: This research is aimed to investigate the influence of corporate social responsibility (CSR) on financial variables such as financial constraints, risks and earnings quality as a mediating aspects for creating firm value. Data were collected from manufacturing companies listed on the Indonesia Stock Exchange for 2013–2016. By using regression and path analysis method, the result shows that CSR has a significant influence on increasing firm value. Meanwhile, the indirect influences show that financial constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 0 publications
3
15
0
7
Order By: Relevance
“…Previous studies indicate the positive roles of socially responsible business conducts on firm’s values (Luo and Bhattacharya, 2006; Mishra and Suar, 2010; Wibowo, 2012) and in helping firm to minimize risks and damaging litigation costs (McGuire et al , 1988). Similar implication was also recognized in the Indonesian setting as past study identified positive influence of corporate social responsibility (CSR) for large firms (Ronald et al , 2019). The present study posits that CSR, as part of the stakeholder’s roles’ provision set by the OECD and the Indonesian GCG codes, is critical for firms.…”
Section: Literature Review and Development Of Hypothesessupporting
confidence: 60%
“…Previous studies indicate the positive roles of socially responsible business conducts on firm’s values (Luo and Bhattacharya, 2006; Mishra and Suar, 2010; Wibowo, 2012) and in helping firm to minimize risks and damaging litigation costs (McGuire et al , 1988). Similar implication was also recognized in the Indonesian setting as past study identified positive influence of corporate social responsibility (CSR) for large firms (Ronald et al , 2019). The present study posits that CSR, as part of the stakeholder’s roles’ provision set by the OECD and the Indonesian GCG codes, is critical for firms.…”
Section: Literature Review and Development Of Hypothesessupporting
confidence: 60%
“…CEO acts as a nexus between the stakeholders and encourages greater CSR engagement rather than being too much concerned about its own benefit (Cai et al, 2011). ESG firms carrying out CSR activities is proved to reduce cash-flow risk and is also being used as an intangible asset for a long-term purpose to benefit the interest of all the stakeholders (Chan et al, 2014;Gao & Zhang, 2013;Miles & Miles, 2013;Mukhtaruddin et al, 2019;Ronald et al, 2019). While CSR represents efforts made by the company to create a positive impact to the internal as well as external stakeholders; ESG disclosure is a systematic assessment of such activities carried out by the organization.…”
Section: Introductionmentioning
confidence: 99%
“…All the properties include elements of social capital in shaping the core value of each hotel. Ronald & Daromes [13] found that CSR has a significant influence on increasing firm value and reducing risks. This finding is in accordance with Chen and Chang [14].…”
Section: Resultsmentioning
confidence: 99%